Coral Reef Damage and Conservation Efforts in North Bali (1997-2005) - Ivan Luttfy Chateriyan; Zeffry Alkatiri (Historia, 2027)
This article describes the environmental history focusing on marine ecosystems such as coral reefs in North Bali from 1997 to 2005. Based on history, the destruction of this coral reef ecosystem has had a major impact on the lives of coastal communities in North Bali. Using historical methods consisting of heuristics, criticism, interpretation, and historiography, this study attempts to answer the question of how coral reefs played an important role for communities in the coastal areas of North Bali in the past. Based on primary sources such as interviews with surviving communities and literature studies, coral reefs played an important role for communities in coastal areas. Their destruction certainly brought disaster and problems that disrupted the lives of communities around the coast who worked as fishermen and tourism operators in Bali. After the impact was felt by the community, there began to be an awareness among the community to carry out conservation efforts that are useful for maintaining the ecological and economic stability of the community in the northern coastal region of Bali.